2004
DOI: 10.1037/0278-7393.30.5.1002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Model-Based and Memory-Based Processing on Speed and Accuracy of Grammar String Generation.

Abstract: Learners are able to use 2 different types of knowledge to perform a skill. One type is a conscious mental model, and the other is based on memories of instances. The authors conducted 3 experiments that manipulated training conditions designed to affect the availability of 1 or both types of knowledge about an artificial grammar. Participants were tested for both speed and accuracy of their ability to generate letter sequences. Results indicate that model-based training leads to slow accurate responding. Memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
44
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 32 publications
5
44
0
Order By: Relevance
“…The results of Domangue et al (2004) can be summarized very simply: Experience-based training led to fast but relatively inaccurate production, and model-based training led to slow production but more accurate knowledge (i.e., participants generated more 100% accurate strings). Integrated training led to intermediate levels of accuracy and speed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The results of Domangue et al (2004) can be summarized very simply: Experience-based training led to fast but relatively inaccurate production, and model-based training led to slow production but more accurate knowledge (i.e., participants generated more 100% accurate strings). Integrated training led to intermediate levels of accuracy and speed.…”
mentioning
confidence: 99%
“…Domangue et al (2004) found that providing participants with a representation of the underlying structure of the grammar at training can enhance accuracy but that production is quite slow. One likely reason is that GR participants had to consult a mental representation of the grammar diagram to guide their generation of exemplars.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When given partial strings, the bottom level or the top level might be used, or the two levels might work together, depending on circumstances. Based the above setup, our simulation succeeded in capturing fairly accurately human data in this task across a set of different circumstances (Domangue et al 2004). In addition, many other tasks have been simulated involving the NACS, including alphabetic arithmetic tasks, categorical inference tasks, discovery tasks, and so on.…”
Section: The Non-action-centered Subsystemmentioning
confidence: 98%
“…Moreover, they were also able to complete partial strings in accordance with their implicit knowledge. The result showed that participants acquired fairly complete implicit knowledge although their explicit knowledge was fragmentary at best (Domangue et al 2004). In simulating this task, while the ACS was responsible for controlling the overall operation, the NACS was used for representing most of the relevant knowledge.…”
Section: The Non-action-centered Subsystemmentioning
confidence: 99%